Transforming Media Accessibility in Europe: Digital Media, Education and City Space Accessibility Contexts - Marcus-Quinn, Ann; Krejtz, Krzysztof; Duarte, Carlos (Springer Nature, 2024)
In a rapidly evolving digital landscape, accessibility in media has emerged as a crucial frontier for inclusion, equality, and knowledge democracy. The present edited volume "Transforming Media Accessibility in Europe: Digital Media, Education and City Space Accessibility Contexts" is a comprehensive exploration of technological, societal, psychological, and legal aspects of media accessibility in Europe. It offers a comprehensive roadmap for navigating the multifaceted landscape of media accessibility. Through compelling experimental studies, case studies, and forward-looking insights, it elucidates the transformative potential of accessible media across diverse sectors, including education, culture, and smart cities. Crafted as a collaborative effort under the COST (European Cooperation in Science and Technology) LEAD-ME Action (CA19142), this book unites the expertise of researchers, educators, and practitioners. This is an open access publication.